Implikasi Filosofis dalam Perkembangan Teknologi Modern - Dongoran, Rosita; Muhammad, Sutan; Siregar, Zul Pahmi; Ananda, Debi; Rahma, Diffani (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The development of science also accompanies the development of modern society. Science that develops and bring schange stohumans that causes problems from material aspects to mental aspects. The rapid development of modern science and technology takes into account the aspectsof systems, values, valuesand religiousvalues, so that moral degradationhas emerged. The purpose of this research is to examine the implications of the philosophy of sciencein the development of modern scientific thics. The method use din this researchis literature study.The discussion analysis shows that the philosophy of science must be integrated philosophically in order to realize scientific functions, especially in moral, intellectual and social aspects.This is because science is neutral and dis agrees with good orbad, considering that it isscience who has the right to determine the attitude. Utilization of science for human set tlement in the operation sof the owner of knowledge an ditscontributi on to the problems of human life. As science develops, it is the philosophy of science that plays a role in realizing good scientific ethics. The existence of the philosophy of science aims to restore sciencein order tocontinue to encourage people to think and be have wisely and wisely.